PREVALENCE OF INSOMNIA AMONG WORKERS IN AN INDUSTRY UTILISING ASBESTOS CONTAINING MATERIALS IN AMBATTUR, TAMIL NADU, INDIA - KUMAR V, DINESH; KUMAR M, BUVNESH; G, DINESH KUMAR; G, NIRMAL KUMAR. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: - Insomnia is a growing public health concern and it is characterised by difficulty in initiating and maintaining sleep. Individuals working in occupations with exposure to respiratory irritants may be at elevated risk of developing insomnia. Objective: To estimate the prevalence of insomnia in an industry utilising asbestos containing materials & to analyse the factors contributing to it. Methodology: A cross sectional study was conducted among 100 workers in an industry utilising asbestos containing materials in Ambattur, Tamil Nadu after getting the IHEC approval & consent. Socio demographic information of the study participants were obtained through a semi structured questionnaire, and the prevalence of insomnia was measured using Insomnia Severity Index (ISI). Collected data was entered in the MS Excel & statistical analysis was done using Jamovi 2.6.4. Socio demographic and environmental characteristics of the study participants were described using descriptive statistics. Frequencies and percentages were used to present categorical data, while continuous data were expressed as mean and standard deviation. The Chi-square test was applied for Statistical analysis, and a p-value of less than 0.05 was considered as statistically significant. Results: The prevalence of insomnia was found to be 23% among the study participants of which 18% were having moderate insomnia, 5% were having severe insomnia based on the ISI questionnaire. 36% of the study participants reported subthreshold insomnia. There was a statistically significant association between age(OR-3.93(95% CI -1.63-9.47), gender (OR-2.991(95%CI=1.079-8.296), travel time(OR=5.639(95%CI= 2.064-15.41), working hours (OR-2.636(95%CI=1.117-6.223, Night shift workers (OR-5.639(95%CI=2.064-15.41) with Insomnia. Conclusion: The findings suggest Insomnia is prevalent among the study participants in an industry utilizing asbestos-containing materials. This study provides important finding of a strong association between occupational, demographic factors and insomnia. These findings underscore the need for occupational health screening and interventions to address sleep disorders this vulnerable population.